Numerical analysis of a new conservative scheme for the 2D generalized Rosenau-RLW equation. Issue 12 (10th September 2021) - Wang, Xiaofeng; Dai, Weizhong; Yan, Yun
Abstract : In this paper, a conservative finite difference scheme to solve the generalized Rosenau-RLW equation in 2D is proposed. The proposed scheme is linear-implicit, mass-preserving, energy-preserving, uniquely solvable, unconditionally stable, and its numerical convergence is of second order in the l ∞ -norm. Results from numerical experiments are reported to demonstrate that the scheme is accurate, efficient and reliable.